2018
DOI: 10.7203/ciriec-e.85.6876
|View full text |Cite
|
Sign up to set email alerts
|

Incorporando el valor social en las licitaciones públicas: un modelo integral

Abstract: RESUMENExiste una creciente preocupación de la sociedad sobre el valor social que se genera o destruye a través de la actividad económica; en el caso de las licitaciones públicas no sólo deberían valorarse los aspectos económicos sino también los sociales. En este trabajo se identifica la problemática vinculada a dicha valoración, se identifican el conjunto de variables implicadas en el valor de los outputs generados, y se propone un modelo que integre valores complementarios al económico. Los cuales se identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
3
0
4
Order By: Relevance
“…In contrast, only a few studies have addressed social issues, despite the recent legislation and the growing emphasis on social considerations within public procurement. Particularly worthy of mention in this area is the work of McCrudden (2004) [4], referred to previously, which analyses the use of public tenders to generate social value, as well as that of Retolaza et al (2015) [2], who posit a social accounting model that includes information on the global value generated by procurement processes, and explicit analyses of social clauses [20]. Worthy of note is the scant importance the term "social" has played in research into public tenders; in fact, no such instances were observed.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, only a few studies have addressed social issues, despite the recent legislation and the growing emphasis on social considerations within public procurement. Particularly worthy of mention in this area is the work of McCrudden (2004) [4], referred to previously, which analyses the use of public tenders to generate social value, as well as that of Retolaza et al (2015) [2], who posit a social accounting model that includes information on the global value generated by procurement processes, and explicit analyses of social clauses [20]. Worthy of note is the scant importance the term "social" has played in research into public tenders; in fact, no such instances were observed.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This approach requires the analysis of the social value generated by the tender process, whereby the output (quality) controls not only consider the value of the goods or services, but also of other outputs that generate social impact, namely risk, social return, social innovation, or emotional value [2]. It is therefore necessary to design a standardized assessment model, guaranteeing its correct application and inclusion in the tender design phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existen varias líneas de investigación que sustentan el interés en este trabajo. Por un lado, una creciente demanda para mejorar la eficiencia en los procesos de compra pública (Falagario et al, 2012), la incorporación de aspectos sociales, además de los económicos, en la valoración de estos procesos (Retolaza et al, 2015c) públicas para conseguir resultados social y medioambientalmente eficientes, (Mendoza, Román & Hernández, 2019). Se avanza hacia la sostenibilidad de las contrataciones desde una perspectiva más amplia que la meramente económica (Walker y Brammer 2009;, pero la apuesta de una administración por la contratación pública sostenible no garantiza su implementación, de hecho, la aplicación de estas políticas en la práctica parece no mantenerse en el tiempo, mostrando que todavía hay diferentes barreras que superar (Grandia & Kruyen, 2020) En el momento actual, la nueva legislación y las nuevas exigencias de la sociedad demandan una mejora en la inclusión de los aspectos sociales en las licitaciones públicas, que pueda permitir un desarrollo estratégico de políticas en esa dirección, como ya se recoge en el trabajo de Akhavan y Beckmann (2017).…”
Section: Estado De La Cuestiónunclassified
“…No tanto porque la generación de dicho valor sea cuestionable, sino porque al tratarse de servicios sociales, provistos en muchas ocasiones a colectivos desfavorecidos, el impacto real generado por las intervenciones no queda reflejado en un mero análisis de corte financiero (Ruiz-Lozano et al, 2020). A raíz de esta constatación, se han desarrollado distintas metodologías de evaluación del valor social (Retolaza et al 2015), con el ánimo de evaluar el impacto que producen las actividades de las organizaciones sociales.…”
Section: Introductionunclassified